The death rate for COVID-19 is positively associated with gross domestic products: Coronavirus and gross domestic product - Lippi, Giuseppe; Henry, Brandon M.; Mattiuzzi, Camilla; Bovo, Chiara (Acta Biomedica Atenei Parmensis, 2020)
N/A - Letter to the Editor